Peer communication and adolescent resilience: An interpersonal approach to mental well-being in the light of Islamic values - Siti Khadijah; Nur Fauziah (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This article aims find out how communication between peers forms adolescent resilience through interpersonal communication patterns using the effectiveness of interpersonal communication according to Maman Rukmana, namely openness, empathy, support, positive attitudes and equality. Methods: This research uses qualitative research with a descriptive research approach. Qualitative research methods focus on in-depth observations of the research object. Findings: The results of the analysis found that Peers having a positive influence will also have a positive impact on teenagers' mental development. Peers can help teenagers in the decision-making process regarding problems experienced by teenagers. It is important for peers to provide full support for teenagers who have mental health disorders. To be able to maintain each other requires closeness to each other. Openness, empathy, support, positive attitudes and equality between teenagers and their peers will build resilience for teenagers who experience mental health problems. Future research is expected to use effectiveness of interpersonal communication process theory and be able to change descriptive qualitative methods into quantitative methods. Conclusion: Interpersonal communication between peers significantly enhances resilience among adolescents with mental health disorders in Bekasi City, as empathy, openness, equality, and positive peer support foster emotional stability, self-acceptance, and recovery. Novelty/Originality of this article: This study uniquely explores how interpersonal communication among peers functions as a therapeutic and empowering mechanism that strengthens resilience and mental well-being among adolescents with various mental health disorders in an Indonesian urban context.